2005
DOI: 10.1002/anie.200501581
|View full text |Cite
|
Sign up to set email alerts
|

Exceptional Molecular Hyperpolarizabilities in Twisted π‐Electron System Chromophores

Abstract: Molecule-based electrooptic (EO) materials are of intense research interest for understanding how light interacts with matter and for applications in photonic technologies such as high-speed optical communications, integrated optics, and optical data processing and storage. [1] In such materials, the second-order susceptibility tensor governing EO response (r 33 ), is governed both by the net polar microstructural order and the microscopic molecular first hyperpolarizability tensor (b). Large b values are esse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
138
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(144 citation statements)
references
References 36 publications
6
138
0
Order By: Relevance
“…Because of strain, the π-systems in teraryl system and in the bridged double bond are twisted. Such a twisted system may thus induce significant enhancement in hyperpolarizability [36,37]. The five-membered heteroaromatic rings in 34 may not only serve as electron donors, but also accommodate the appropriate geometry to enable the interactions between the oligoaryl systems and the double bond, leading to unusual photophysical and NLO properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of strain, the π-systems in teraryl system and in the bridged double bond are twisted. Such a twisted system may thus induce significant enhancement in hyperpolarizability [36,37]. The five-membered heteroaromatic rings in 34 may not only serve as electron donors, but also accommodate the appropriate geometry to enable the interactions between the oligoaryl systems and the double bond, leading to unusual photophysical and NLO properties.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, one might consider that the bridging alkene group might be an electron acceptor. Recently, it has been shown that twisted π-electron system chromophores in a biaryl system having charged donor and acceptor moieties exhibit ultralarge molecular hyperpolarizability with exceptionally high µβ values [36,37]. It is envisaged that 34 and related compounds may be second-order NLO active.…”
Section: Second-order Nonlinear Optical Properties Of [N2]cyclophenesmentioning
confidence: 99%
“…In octopolar NLO compounds, non-centrosymmetric molecules with no dipole moment, however, a significant increase in second order NLO performance, when compared to chromophores designed after the "traditional" push-pull approach, has not been achieved to date. A new paradigm for the optimization of molecular hyperpolarizabilities has been recently proposed by the use of "twisted" D--A chromophores [14]. These molecular modules (compound 4 in Fig.…”
Section: Discussion "State Of the Art" Design Principles For Efficienmentioning
confidence: 99%
“…[5][6][7][8] The performance of a molecule is evaluated by comparing its response with that of the optimal structure that uses the same number of electrons * jperezmo@skidmore.edu (the quantum limit). An analysis based on the quantum limit theory applied to experimental data allows one to determine the mechanisms that dominate the nonlinear optical response at the molecular level, [9][10][11][12][13][14][15][16][17][18] introduce new paradigms for optimization, [14,[19][20][21][22][23][24] and establish fundamental scaling laws. [25,26] In this paper we introduce a new analysis that we apply to experimental data in the literature to identify the best molecular candidates for the largest second-order nonlinear optical response.…”
Section: Introductionmentioning
confidence: 99%